Boston Scientific and Medinol : a bad alliance leads a company to do stupid things - Nagy, Andrea; Oster, Sharon M. ([London] : SAGE, 2016)
Boston Scientific and Medinol sought a mutually beneficial alliance, signing a ten-year agreement that Boston Scientific would distribute and market Medinol's stents. But the alliance quickly deteriorated and, before the parties would finally reach a court settlement in 2005, there would be layoffs and recalls, suits and countersuits, threats to cut off manufacturing and the construction of a secret factory in Ireland. This case explains how a business relationship, created with the best of intentions, could go badly awry.
Originally Published in: Nagy, A., & Oster, S. (2006). Boston Scientific and Medinol: A Bad Alliance Leads a Company to Do Stupid Things. 06-012. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Boston Scientific Corporation; Medinol (Firm); Strategic alliances (Business) -- Case studies; Strategic alliances (Business) -- Law and legislation -- Case studies; Negotiation in business -- Case studies